Calatonia e religiosidade: uma abordagem junguiana - Armando, Marilena Dreyfuss (2007)
The aim of this study was to investigate Calatonia, a method of relaxation developed by Pethö Sándor, as a means to contact the numinous. An account of Pethö Sándor s life was presented, as well as a description of the method which he created, namely Calatonia. Numinous is the term which Carl Gustav Jung chose to refer to what he understands as religiosity, which, according to him, is the transforming experience of contact with archetypes; a momentously dynamic effect that does not depend on one s will. In order to develop this study, qualitative research was preferred as a method of investigation and interpretation once it focuses on the understanding of phenomena. Eleven psychologists, ranging from 26 to 58 years of age, participated in this research, which started off from the observations made by two participants. Such observations were interpreted in the light of Jung s constructive method, and the resulting data was analyzed through the application of Forghieri s method. It has been c oncluded that Calatonia may facilitate contact with the numinous, seeing that some evidence of this contact was detected in the two cases analyzed. It is possible to deduct thereof that the lowering of ego activity facilitated by Calatonia may promote the emergence of images charged with numinosity, which, once integrated to a structured ego, may lead to a transformation orientated to a repositioning which ultimately proves favorable to a change of attitude towards life